Prevalence of Listeria monocytogenes in European cheeses: A systematic review and meta-analysis. (February 2018) - Martinez-Rios, Veronica; Dalgaard, Paw
Abstract: Both in Europe and worldwide cheese has caused important outbreaks of listeriosis and can be a vehicle for transmission of Listeria monocytogenes to consumers. A systematic review and meta-analysis were conducted using scientific literature and European Food Safety Authority (EFSA) reports to summarize available data on the prevalence of L. monocytogenes in different types of cheeses produced in Europe. Meta-analysis models were used to estimate mean prevalence of the pathogen and to compare prevalence among types of cheeses (fresh, ripened, veined, smear and brined) and cheeses produced using, respectively, pasteurized or un-pasteurized milk. Data from a total of 130, 604 samples were analysed. Mean prevalence for presence during 2005–2015 estimated from scientific literature (2.3% with confidence interval (CI): 1.4–3.8%) was more than three times higher than results from EFSA reports (0.7%; CI: 0.5–1.1%). The prevalence differed among types of cheeses including fresh (0.8%; CI: 0.3–1.9%), ripened (2.0%; CI: 0.8–4.9%), veined (2.4%; CI: 0.9–6.3%), smear (5.1%; CI: 1.9–13.1%) and brined (11.8%; CI: 3.5–33.3%). Mean prevalence of L. monocytogenes in soft/semi-soft cheeses were not significantly different (P > 0.05) for cheeses produced from pasteurized (0.9%; CI: 0.4–1.9%) or un-pasteurized (1.0%; CI: 0.4–2.2%) milk. For cheese samples reported by EFSA 0.2% CI: 0.1–0.4% had concentration of L. monocytogenes above the critical European limits of 100 cfu/g. In addition, this systematic review focused on groups/species of microorganisms suitable as indicator organisms for L. monocytogenes in cheeses to reflect the level of production hygiene or as index organisms to assess the prevalence of L. monocytogenes in cheeses. However, no suitable indicator or index organisms were identified. The performed meta-analyses improved our understanding of L. monocytogenes prevalence in different types of cheeses and provided results that can be useful as input for quantitative microbiological risk assessment modelling. Highlights: Overview of listeriosis outbreaks caused by cheese 1983–2016. Overall prevalence of L. monocytogenes in European cheese 2005–2015. Prevalence of L. monocytogenes in different types of cheese. No indicator or index organism identified for L. monocytogenes in cheese.